2015
DOI: 10.1016/j.nbt.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipid biosurfactants: Possible uses as antibacterial and antibiofilm agent

Abstract: Biosurfactants are amphipathic, surface-active molecules of microbial origin which accumulate at interfaces reducing interfacial tension and leading to the formation of aggregated micellular structures in solution. Some biosurfactants have been reported to have antimicrobial properties, the ability to prevent adhesion and to disrupt biofilm formation. We investigated antimicrobial properties and biofilm disruption using sophorolipids at different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
101
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(117 citation statements)
references
References 36 publications
6
101
0
3
Order By: Relevance
“…Several reports have demonstrated the ability of biosurfactants to inhibit and/or kill microorganisms, for example, with natural lipopeptides (Banat, Díaz De Rienzo and Quinn 2014;Cochrane et al 2015), rhamnolipids (Díaz De Rienzo et al 2016a,b) and Sophorolipids (Díaz de Rienzo et al 2015Rienzo et al , 2016c. It has also been reported that they are able to alter a substrate's surface energy (Busscher and van der Mei 1997) and increase surface area (Rodrigues et al 2006), which would make biosurfactants important potential candidates for oral health-related applications.…”
Section: Potential Biosurfactant Applications For Oral Health and Hygmentioning
confidence: 99%
“…Several reports have demonstrated the ability of biosurfactants to inhibit and/or kill microorganisms, for example, with natural lipopeptides (Banat, Díaz De Rienzo and Quinn 2014;Cochrane et al 2015), rhamnolipids (Díaz De Rienzo et al 2016a,b) and Sophorolipids (Díaz de Rienzo et al 2015Rienzo et al , 2016c. It has also been reported that they are able to alter a substrate's surface energy (Busscher and van der Mei 1997) and increase surface area (Rodrigues et al 2006), which would make biosurfactants important potential candidates for oral health-related applications.…”
Section: Potential Biosurfactant Applications For Oral Health and Hygmentioning
confidence: 99%
“…The hydroxy fatty acids are generally 16 or 18 carbon atoms in length and may possess multiple olefinic groups. SLs have been shown to possess various antimicrobial properties against bacteria and fungi (Lang and Wagner, 1993; Kitamoto et al, 2002; Ashby et al, 2011; De Rienzo et al, 2015; Zhang et al, 2016). The antibacterial activity of SLs against Rhodococcus erythropolis , Bacillus subtilis , Staphylococcus epidermidis , Streptococcus agalactiae , Moraxella sp., Pseudomonas putida , Enterobacter aerogenes , and E. coli was evaluated by Shah et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that physicochemical and biological properties of SLs are significantly influenced by the distribution of the lactone vs. free-acid forms in the fermentative broth (Van Bogaert et al, 2007; Sleiman et al, 2009; De Rienzo et al, 2015; Maddikeri et al, 2015). The specific fatty acids used in the growth medium also influence the composition of SLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLs possess a sophorose backbone structure with a variety of acyl groups at the 6 and 6′-positions, and a hydroxyl fatty acid. 1,4) These compounds have excellent surface active properties, and they exhibit antimicrobial, 10,11) anticancer, 12) and antiviral activities. 13) They are also highly biodegradable in the environment.…”
mentioning
confidence: 99%